2000
DOI: 10.1128/mcb.20.4.1116-1123.2000
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Chloroplast psbA mRNA Is Modulated in the Light by Counteracting Oxidizing and Reducing Activities

Abstract: Light has been proposed to stimulate the translation of Chlamydomonas reinhardtii chloroplast psbA mRNA by activating a protein complex associated with the 5 untranslated region of this mRNA. The protein complex contains a redox-active regulatory site responsive to thioredoxin. We identified RB60, a protein disulfide isomeraselike member of the protein complex, as carrying the redox-active regulatory site composed of vicinal dithiol. We assayed in parallel the redox state of RB60 and translation of psbA mRNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
113
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 59 publications
2
113
1
Order By: Relevance
“…In vitro and in organello studies showed that the binding activity of this complex and the resulting psbA translation are increased under reducing conditions, such as in the light (Fig. 4), when D1 protein is needed most [24,25]. Recent results demonstrate that this light activation is mediated by two signals: a 'priming' signal generated by the PQ pool and a dithiol signal from thioredoxin.…”
Section: Inner-chloroplastic Transduction Of Photosynthetic Redox Sigmentioning
confidence: 98%
“…In vitro and in organello studies showed that the binding activity of this complex and the resulting psbA translation are increased under reducing conditions, such as in the light (Fig. 4), when D1 protein is needed most [24,25]. Recent results demonstrate that this light activation is mediated by two signals: a 'priming' signal generated by the PQ pool and a dithiol signal from thioredoxin.…”
Section: Inner-chloroplastic Transduction Of Photosynthetic Redox Sigmentioning
confidence: 98%
“…In comparison, redox states of Trxs and the NADPH pool have been implicated in the coordination of stromal activity and in feedback regulation of the membranal reactions of photosynthesis (Johnson, 2003;Martinsuo et al, 2003;Hald et al, 2008;Schürmann and Buchanan, 2008). Several studies of the state transition phenomenon (Tikkanen et al, 2010), of the translation of the chloroplast psbA mRNA (Trebitsh et al, 2000;Trebitsh and Danon, 2001), and of chloroplast transcription (Pfannschmidt and Liere, 2005;Lemeille et al, 2009;Steiner et al, 2009) further suggested a cooperative regulation of the plastoquinone and the Trx pathways. This cooperative regulation is most likely important for maintaining a critical balance between the production of reducing equivalents by the light reactions and their consumption by stromal activity to avoid generating detrimental ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Defining the oxidizing activity and the time at which it occurs could also be important for discerning the biological context of the redoxregulated phenomenon. Trx-regulated proteins are generally oxidized in the dark and are reduced upon illumination (Schürmann and Buchanan, 2008), but a Trx-implicated oxidizing activity was also found in the light (Trebitsh et al, 2000;Martinsuo et al, 2003), indicating a broader regulatory role for protein thiol oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…This complex binds to the 5Ј untranslated region of the chloroplast psbA mRNA, where it is thought to regulate the translation of the downstream ORF in response to photosynthetic and light signals (1)(2)(3). RB60 controls the assembly of the regulatory protein complex on psbA mRNA through two mechanisms (1,2,(4)(5)(6). In the first, complex assembly is stimulated by the reduction, and diminished by the oxidation, of vicinal disulfide groups in RB60 (2,6).…”
mentioning
confidence: 99%